"Better the devil you know": Are stated preferences over health and happiness determined by how healthy and happy people are?. (June 2022) - Adler, Matthew D.; Dolan, Paul; Henwood, Amanda; Kavetsos, Georgios
Abstract: Most people want to be both happy and healthy. But which matters most when there is a trade-off between them? This paper addresses this question by asking 4000 members of the UK and US public to make various choices between being happy or being physically healthy. The results suggest that these trade-offs are determined in substantial part by the respondent's own levels of happiness and health, with unhappy people more likely to choose unhappy lives and unhealthy people more likely to choose unhealthy ones: "better the devil you know, than the devil you don't". Age also plays an important role; older people are more likely to choose being healthy over being happy. Information about adaptation to physical health conditions matters too, but less so than respondent characteristics. These results further our understanding of public preferences with important implications for policymakers concerned with satisfying those preferences. Highlights: Most people want to be both happy and healthy, but which matters most? We trade-off levels of happiness and physical health in the UK and the US. Choices are determined by respondents' own levels of happiness and health. Information about adaptation to physical health conditions matters too. The results have implications for policymakers seeking to satisfy those preferences.